2015
DOI: 10.1111/poms.12375
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Challenge of Modeling for Decision‐Making in Socially Responsible Operations

Abstract: Companies seek sustainability by combining the quest for profitability with the pursuit of social responsibility. Since socially responsible operations are characterized by the presence of multiple stakeholders with conflicting goals, applying classical optimization models would seem premature; we first need to capture the behavior of the entire system before attempting to optimize sub‐systems to ensure that we focus on the ones driving the behavior of interest. Alternative methodologies are required if we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 70 publications
(111 reference statements)
2
88
0
Order By: Relevance
“…It is no longer solely a matter of logistics or SCM but a much broader, multistakeholder, multidiscipline problem setting. We should be ready to take a holistic system view and include different methods, like field work, case research, simulation/system dynamics (SD), and econometric models in a complimentary way (Besiou and Van Wassenhove 2015). This has a large potential positive impact on the relevance of our work, especially if we are ready to extend our modus operandi and skillfully integrate knowledge from other disciplines.…”
Section: A World Of Opportunity For Or/om Researchersmentioning
confidence: 99%
“…It is no longer solely a matter of logistics or SCM but a much broader, multistakeholder, multidiscipline problem setting. We should be ready to take a holistic system view and include different methods, like field work, case research, simulation/system dynamics (SD), and econometric models in a complimentary way (Besiou and Van Wassenhove 2015). This has a large potential positive impact on the relevance of our work, especially if we are ready to extend our modus operandi and skillfully integrate knowledge from other disciplines.…”
Section: A World Of Opportunity For Or/om Researchersmentioning
confidence: 99%
“…The three pillars of sustainability are the basis of the triple bottom line approach (3BL), which has been used by researchers and practitioners (Besiou & Van Wassenhove, 2015). In the context of sustainable supply chain management, it involves looking beyond the traditional economic parameters and making decisions based on life cycle costs, associated environmental and social risks and benefits and broader social and environmental implications (Tchokogué et al, 2018).…”
Section: Sustainable Scmmentioning
confidence: 99%
“…By reporting CSR on a yearly basis, companies show that their concerns are not limited only to economic benefits and profits, but also include the needs of the society, economy, environment and stakeholders. Nowadays CSR is seen as guarantee of sustainable development [16,36]. Moreover, recent analysis of CSR consciousness of the supply-chain members on the supply-chain's decision showed that the stronger the awareness of CSR among its stakeholders and general public, the more the consumer surplus and involvement is received, and even moderate CSR awareness improves the overall sustainability state of the supply chain [30].…”
Section: Sustainable Supply Chains and Standards For Their Evaluationmentioning
confidence: 99%